(untitled) (FUDMA JOURNAL OF SCIENCES, 2022)
Appropriate and efficient technology is desired to obtain clean groundnut kernels for further processing such as edible oil extraction and for meeting international export standard. An existing groundnut decorticator was modified and a proto-type was constructed to decorticate groundnut in-shell with minimum kernel damage. The modified decorticator was tested with Samnut 14 groundnut variety at 20 mm concave clearance. The groundnuts in-shell was graded into three grades (grades I, II and III) while screen apertures of 8, 10 and 12 mm were used at 8, 10 and 20 % moisture levels using three replications in a complete randomized design. The components of the decorticator include the hopper, frame, decorticating drum, main shaft, blower, pulleys, belt, bearings and a 5 kW electric motor. Results obtained showed a high decorticating efficiency of 94.66% of clean kernels at 10% moisture content was obtained from grade III samples using 8 mm screen aperture. The least kernel bruises and splits of 2.08 and 1.37%, respectively were recorded at 8% moisture level and 12 mm aperture from grade II samples. These results reduced the high incidence of aflatoxin contamination on the decorticated kernels, thus increasing the kernel’s value as well as making it less carcinogenic.